Abnormal thymic stromal lymphopoietin expression in the duodenal mucosa of patients with coeliac disease. Issue 10 (4th September 2015) - Biancheri, Paolo; Di Sabatino, Antonio; Rescigno, Maria; Giuffrida, Paolo; Fornasa, Giulia; Tsilingiri, Katerina; Pender, Sylvia L F; Papadia, Cinzia; Wood, Eleanor; Pasini, Alessandra; Ubezio, Cristina; Vanoli, Alessandro; et al.
Abstract : Objective: The short isoform of thymic stromal lymphopoietin (TSLP), a cytokine constitutively expressed by epithelial cells, is crucial in preserving immune tolerance in the gut. TSLP deficiency has been implicated in sustaining intestinal damage in Crohn's disease. We explored mucosal TSLP expression and function in refractory and uncomplicated coeliac disease (CD), a T-cell-mediated enteropathy induced by gluten in genetically susceptible individuals. Design: TSLP isoforms—long and short—and receptors—TSLPR and interleukin (IL)-7Rα—were assessed by immunofluorescence, immunoblotting and qRT-PCR in the duodenum of untreated, treated, potential and refractory patients with CD. The ability of the serine protease furin or CD biopsy supernatants to cleave TSLP was evaluated by immunoblotting. The production of interferon (IFN)-γ and IL-8 by untreated CD biopsies cultured ex vivo with TSLP isoforms was also assessed. Results: Mucosal TSLP, but not TSLPR and IL-7Rα, was reduced in untreated CD and refractory CD in comparison to treated CD, potential CD and controls. Transcripts of both TSLP isoforms were decreased in active CD mucosa. Furin, which was overexpressed in active CD biopsies, was able to cleave TSLP in vitro. Accordingly, refractory and untreated CD supernatants showed higher TSLP-degrading capacity in comparison to treated CD and control supernatants. In our ex vivo model, both TSLP isoforms significantly downregulated IFN-γ and IL-8 production by untreated CD biopsies. Conclusions: Reduced mucosal TSLP expression may contribute to intestinal damage in refractory and untreated CD. Further studies are needed to verify whether restoring TSLP might be therapeutically useful especially in refractory patients with CD.